Evaluation of anti-Mullerian hormone as parameter of ovarian function in patients with systemic lupus erythematosus: A systematic review and meta-analysis - Nooryanto, Mukhammad; Wulandari, Wulandari (Universitas Airlangga, 2024)
HIGHLIGHTS Systemic lupus erythematosus (SLE) patients show a strong correlation between Anti-Mullerian Hormone (AMH) levels and ovarian function. Lower AMH levels indicate higher risk of impaired ovarian function and diminished reserve, as revealed by this meta-analysis. The comprehensive synthesis of available data in this study has important clinical implications for the management and counseling of systemic lupus erythematosus (SLE) patients. ABSTRACT Objective: The assessment of ovarian function in patients with systemic lupus erythematosus (SLE) holds paramount importance for both clinicians and patients. This systematic review and meta-analysis delves into the role of anti-Mullerian hormone (AMH) as a key marker in evaluating ovarian function among SLE patients. Our study aimed to provide valuable insights for clinicians managing ovarian function assessments and to offer practical recommendations for differences in therapy for patient care. Materials and Methods: Studies comparing serum AMH levels between patients with systemic lupus erythematosus and healthy controls, as well as serum AMH levels between SLE patients, are necessary. PRISMA guidelines were used for this systematic review. Databases like PubMed, SCOPUS, EuropePMC, ProQuest, and Cochrane Central were searched using specific terms (